Platelet Activation Is Not Always Associated With Platelet-Related Plasma microRNA Abundance – Results From a Randomized Controlled Trial of Periodontal Patients - Heber, Stefan; Laky, Markus; Anscheringer, Isabella; Wolschner, Lukas; Mussbacher, Marion; Krammer, Teresa; Haririan, Hady; Schrottmaier, Waltraud C.; Volf, Ivo; Hackl, Matthias; Moritz, Andreas; Assinger, Alice (Frontiers in Physiology, 2021)
Platelets are involved in a variety of diseases, making their adequate functional assessment is essential. However, due to their easily activatable nature this has some methodological pitfalls. Therefore, the availability of stable, easily measurable surrogate markers would be beneficial. In this regard, some evidence suggests that certain microRNAs (miRNAs) circulating in plasma might be useful. We aimed to corroborate their suitability by analyzing plasma samples obtained in a randomized controlled trial, which assessed the effects of periodontal treatment on platelet function. We hypothesized that miRNA levels mirror changes of platelet activation and -function. Both platelet function and miRNA abundance were quantified using state-of-the-art flow cytometry and qPCR methods. The following miRNAs were quantified: 223-3p, 150-5p, 197-3p, 23a-3p, 126-3p, 24-3p, 21-5p, 27b-3p, 33a-5p, 320a, 191-5p, 28-3p, 451a, 29b-3p and 1-3p. However, periodontal treatment did not affect the abundance of any investigated miRNAs to a relevant extent. Platelet activation and reactivity indices did neither correlate with any tested miRNA at baseline, nor after the treatment period. In addition, there was no evidence that investigated miRNAs were released by platelets, as suggested previously. In conclusion, our data suggest that in patients suffering from periodontal disease the investigated miRNAs are unlikely to be suitable biomarkers for platelet function. Our data aim to raise awareness that previously determined platelet activation dependent circulating miRNAs are not suitable as platelet biomarkers in all cohorts.